Alternative to antibiotics against Pseudomonas aeruginosa: Effects of Glycyrrhiza glabra on membrane permeability and inhibition of efflux activity and biofilm formation in Pseudomonas aeruginosa and its in vitro time-kill activity. (September 2016) - Chakotiya, Ankita Singh; Tanwar, Ankit; Narula, Alka; Sharma, Rakesh Kumar
Abstract: The multi-drug resistance offered by Pseudomonas aeruginosa to antibiotics can be attributed towards its propensity to develop biofilm, modification in cell membrane and to efflux antibacterial drugs. The present study explored the activity of Glycyrrhiza glabra and one of its pure compounds, glycyrrhizic acid against P. aeruginosa and their mechanism of action in terms of the effect on membrane permeability, efflux activity, and biofilm formation were determined. Minimum inhibitory concentrations were determined by using broth dilution technique. The minimum bactericidal concentrations were assessed on agar plate. The MIC of the extract and glycyrrhizic acid was found to be 200 and 100 μg ml −1, respectively. The MBC was found to be 800 and 400 μg ml −1 in the case of extract and glycyrrhizic acid, respectively. Time -dependent killing efficacy was also estimated. Flowcytometric analysis with staining methods was used to determine the effect of extract and glycyrrhizic acid at 2 × MIC on different physiological parameters and compared it with the standard (antibiotic). The growth of P. aeruginosa was significantly inhibited by extract and the pure compound. The herbal extract and the glycyrrhic acid were also found to effective in targeting the physiological parameters of the bacteria that involve cell membrane permeabilization, efflux activity, and biofilm formation. This study reports the antipseudomonal action of Glycyrrhiza glabra and one of its compound and provides insight into their mode of action. Highlights: Glycyrrhiza glabra have shown the MIC and MBC at 200 and 800 µg ml −1, while glycyrrhizic acid have shown the inhibitory and bactericidal effect at 100 and 400 µg ml −1 . Time-kill profile of glycyrrhizic acid was found to be similar to the standard, amikacin after 4 h in both the cases. The bactericidal activity of herbal extract was observed after 12 h. The highest percentage of Propidium Iodide stain retention was found with glycyrrhizic acid treatment i.e, 63.9 ± 2.109% followed by crude extract treated cell (50.4 ± 1.009%) then amikacin treated cells (48.3 ± 1.04%). Ethidium Bromide staining revealed that 56.8 ± 2.08% of cells stained after exposure to extract, followed by glycyrrhizic acid treated cells (43.9 ± 2.109%) then amikacin treated cells (48 ± 1.009%). Highest inhibition of biofilm formation was found by 88.63 ± 4.83 % with the standard, ciprofloxacin followed by herbal extract (83.35 ± 4.33 %) and glycyrrhizic acid (82.72 ± 0.20 %) at 200 μg ml −1 .